Development and evaluation of a multiplex assay to measure bovine IgG1 and IgG2 using microspheres and flow cytometry - Kempegowda, Rekha (Kansas State University, 2005)
Failure of passive transfer (FPT) is one of the main reasons for increased mortality rate in newborn calves and diagnosis is dependent on determination of serum IgG concentrations (diagnosis is based on < 1 g/dL of total IgG). Several qualitative assays are available, but the reference method, single radial immunodiffusion assay (SRID), albeit quantitative measures only one subclass at a time. We set out to develop a competitive multiplex microsphere flow cytometry assay to measure bovine IgG1 and IgG2 concentrations in 30 serum samples acquired from newborn Holstein calves prior to and 24 hours after ingestion of colostrum and to compare the values with SRID. A triplex bead assay was created by mixing three distinct sets of Quantum plex carboxylated fluorescent microspheres that were coated with purified bovine IgG1, IgG2 or albumin using a two step chemical reaction. The triplex protein coated beads were reacted with a cocktail of sheep anti-bovine IgG1 and IgG2. Evaluation of analytical specificity demonstrated cross reactivity between anti-bovine IgG2 and IgG1 coated beads that precluded determination of IgG2 > 0.5 g/dL. Cross reactivity between anti-IgG1 and IgG2 coated beads was minimal and did not affect IgG1 concentrations between 0.15 to 1.2 g/dL. A competitive linear decrease in the fluorescence intensity was observed in the triplex assay when 2-fold dilutions spanning a concentration range of 12 mg/dL – 100 mg/dL of either purified bovine IgG1 or IgG2 were included as a competitive inhibitor of the reaction. Precolostral serum samples from 29 calves were determined to be < 0.4 g/dL by SRID. Standard calibrants for the flow assay were prepared from two fold serial dilutions of purified bovine IgG (stock concentration 10 g/dL) using a precolostral calf serum pool as the diluent. The standard calibrants (IgG1 was 1.0- 0.16 g/dL and IgG2 was 3.4 – 0.22 g/dL) were used as the inhibitors in a triplex assay to develop a standard curve for unknown samples. Dilutions of bovine reference serum containing known amounts of IgG1 (1.2 – 0.15 g/dL) and IgG2 (1.6 – 0.2 g/dL) was used as positive control. The intra Intra-assay and inter-assay precision of the mutiplex assay was good (coefficient of variation < 10%). Since the IgG2 concentrations of post colostral samples were below detection limit, only IgG1 values were compared to the SRID. The agreement between triplex microsphere assay and SRID for IgG1 was poor with a mean bias of 0.743 g/dL towards triplex microsphere assay (95% confidence interval of 0.382 to 1.105 g/dL). Method comparison studies between total IgG determined by SRID and the gamma-globulin fraction determined by serum electrophoresis indicated that the SRID calculated higher values than the protein method (mean bias of -1.4 g/dL, 95% confidence interval was -1.8 to -1.05 g/dL). We hypothesized that the positive bias for the microsphere assay was explained in part by the use of dilution factors, use of standards that had a low analytical range, and erroneously high standards used in the SRID method.
Keywords: Bovine IgG1; Bovine IgG2; Biology, Animal Physiology (0433)